Immunohistochemical distribution of irisin in the lung and tongue of Porcupine (Hystrix cristata) - Gur, F. M.; Timurkaan, S.; Yalcin, M. H.; Tarakci, B. Gencer (Agricultural Research Communication Centre, 2017)
Irisin, a novel peptide, was first identified in skeletal muscle cells. It is an exercise protein that is secreted into the bloodstream, through which it reached the white adipose tissue, and interacted with an unknown receptor and cause fat destruction by converting the white adipose tissue to brown adipose tissue. The presence of irisin immunoreactivity in porcupine lung and tongue was studied. In lung, irisin immunoreactivity was found in type II pneumocytes,qa bronchus, bronchioles and blood vessel. Positive irisin immunostaining was also detected in the lamina epithelialis, striated muscle cells and serous glands in porcupine's tongue. The function of locally synthesized irisin is currently unknown. Therefore, further study is required to reveal the precise effect of irisin.
Keywords: Immunoreactivity; Irisin; Lung; Porcupine; Tongue